DIVERSIFIKASI PRODUK GAYOR BALI GUNA MENINGKATKAN DAYA SAING - Putu Fajar Kartika Lestari; Ida Bagus Swaputra; Ida Ayu Budhananda Munidewi (Seminar Nasional Aplikasi Iptek (SINAPTEK), 2019)
ABSTRACT "Gayor Bali" is the result of home industry crafts that produce art items in the form of gayor / decoration located at the entrance which has been more for traditional ceremonial and other religious activities for Hindus in Bali. Gayor as a set of wedding ceremonies and other traditional works that are placed in the angkulangkul / entrance gate of the house that serves to beautify the decoration of the location of the event. Gayor Bali changed with the development of the era, in the past Gayor was made of mushrooms and decorated with gumitir flowers or other flowers, but gradually the material for Gayor used cork material, so that the appearance of angkul-angkul became more elegant. The problem is never knowing for certain whether the business is profitable or not. The purpose of the PKM program is to improve partner retention and skills in bookkeeping and business management techniques, marketing techniques and to improve partner knowledge. The method used in achieving these objectives is training and assistance in making a business accounting system based on simple accounting techniques; The program outputs are Cash Book, Inventory Book, Production Cost Calculation (HPP), Breakeven Calculation (BEP), Marketing Techniques, and articles that are ready to be published in scientific journals. Keywords: Gayor Bali; Simple Bookkeeping; COGS